Bromelain-loaded Dextran Hydrogels Crosslinked with Schiff Base Chemistry: Synthesis, pH-Dependent Biodegradability and Antibacterial Activity - Aras, Hatice; Uner, Bukre Kiran; Abamor, Emrah Sefik; Elalmis, Yeliz Basaran; Topuzogullari, Murat (INST TECNOLOGIA PARANA, 2025)
Antibacterial materials such as films and hydrogels have gained considerable interest in combating pathogenic bacteria by reducing bacterial populations. In this paper, we produced dextran-based hydrogels and incorporated them with the partial purified bromelain enzyme, which inhibits bacterial growth. The hydrogels were produced by cross-linking the dextran aldehyde derivative with ethylenediamine and bovine serum albumin (BSA) via Schiff base reaction using cryogelation technique. The incorporated bromelain enzyme was partially purified, exhibiting 9-fold increase in enzymatic activity and 18-fold increase in protein content compared to the crude extract. The produced hydrogels were characterized using Fourier Transform Infrared Spectroscopy (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), swelling, and degradation studies. The hydrogels exhibited a swelling behavior of approximately 625% over 8 hours and a degradation behavior of 77.4% and 9.43% at pH 5 and pH 7 over 4 weeks, respectively. Release studies showed that approximately 10% of the initially loaded enzyme was released from the hydrogels after 8 hours. The results of MTT assay revealed that neither the free nor enzyme-loaded hydrogel displayed significant toxicity against L929 cells. Furthermore, the antibacterial activity of enzyme-loaded hydrogels demonstrated a strong antibacterial effect against both S. aureus and E. coli compared to the bare hydrogel, indicating their potential for antibacterial applications. As a result, a multifunctional hydrogel with pH-dependent biodegradation, biocompatibility, antibacterial properties, and enzyme release capability has been developed for potential biomedical applications.
Keywords: antibacterial applications; cryogel; enzyme; immobilization; Schiff base; ALDEHYDE; CRYOGELS; GELATIN; STARCH; Life Sciences & Biomedicine - Other Topics